The theory of human capital as the basis of the economy of labor - Leputa, Natalia (SPC Journal of Education, 2020)
The aim of this article is to show how well-known and respected economists with different background have perceived capital and economy over the centuries. Particular attention has been paid to the history of economics and the importance of human capital, which should be con-tinuously expanded and deepened in order to develop new skills needed, for example in future work, but also the attention will focus on several formulas which are used to calculate capital.Â Â